HFC‐43‐10mee atmospheric abundances and global emission estimates. Issue 6 (26th March 2014) - Arnold, Tim; Ivy, Diane J.; Harth, Christina M.; Vollmer, Martin K.; Mühle, Jens; Salameh, Peter K.; Paul Steele, L.; Krummel, Paul B.; Wang, Ray H. J.; Young, Dickon; Lunder, Chris R.; Hermansen, Ove; et al.
Abstract We report in situ atmospheric measurements of hydrofluorocarbon HFC‐43‐10mee (C5H2F10; 1, 1, 1, 2, 2, 3, 4, 5, 5, 5‐decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2‐eq yr−1 based on a 100 year global warming potential of 1660). HFC‐43‐10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.